Hypovitaminosis D in a Young Lebanese Population: Effect of GC Gene Polymorphisms on Vitamin D and Vitamin D Binding Protein Levels. (25th September 2015) - Medlej‐Hashim, Myrna; Jounblat, Rania; Hamade, Aline; Ibrahim, Jose Noel; Rizk, Francine; Azzi, Georges; Abdallah, Marwa; Nakib, Layane; Lahoud, May; Nabout, Rita
Summary Bioactive vitamin D is a steroid hormone transported in blood via the vitamin D binding protein (DBP). Our study aimed to investigate the vitamin D status in a young Lebanese population and study the association of hypovitaminosis with levels of DBP. Polymorphisms in the GC gene that encodes DBP were also screened. Blood samples were collected from 179 university students. Vitamin D status and DBP levels were assayed by enzyme‐linked immunosorbent assay (ELISA). DNA was extracted from 128 participants, and genotyping of the two GC gene SNPs, rs7041, and rs4588, was carried out by restriction fragment length polymorphism. Forty‐seven percent of participants had hypovitaminosis D (<20 ng/ml). A significant positive correlation was observed between vitamin D status and DBP. Genotyping data showed that participants carrying the rs7041 GG and rs4588 AA genotypes had higher concentrations of DBP than those carrying other genotypes. Four allelic versions of the GC gene were observed, one of which, GC*3, was encountered for the first time in this study, and was found to be associated with both normal vitamin D and high DBP levels. Modifying genes such as GC could therefore affect DBP levels, and contribute, along with environmental factors, to the hypovitaminosis D observed in sunny countries.